The new public management from the point of view of the institutional approach, as a factor for strengthening cooperative law: The case of Mexico in the period 2012-2018 - Barragán Fernández, Omar (Cooperativismo & Desarrollo, 2022)
Purpose: The purpose of the presentation is to analyze cooperative law in Mexico, considering the New Public Management (NPM) of said country during the period 2012-2018, in which the federal government undertook structural reforms within its scheme of social programs and in which there were relevant legal reforms that did not necessarily go beyond that. Description: The topic focuses on the fact that, although there was a relevant institutional change in 1994 with the General Law of Cooperative Societies, which raised an NPM in that sense, there were reforms in 2018 that did not show progress beyond the framework legal. Points of view: From the point of view of whoever writes this, cooperative legislation has shown progress in formality, not in the operational reality of Mexico, considering the paths of the NPM in that sense. Conclusions: therefore, it is concluded that there is a need to make the reality of cooperative law clearer in social and solidarity schemes from government action, since there are institutional bases in this regard.